Age dynamics of indicators of the microcirculation system in students according to laser dopler flowmetry - Gorna, Оksana; Horban, Daria (ScienceRise: Biological Science, 2022)
The article is devoted to the problem of studying blood microcirculation in healthy individuals at different stages of ontogenesis. The aim of the study was to investigate the peculiarities of the skin blood flow in students aged 17-21. Materials and ways of the research. In order to study the functional state of blood microcirculation the method of laser Doppler flowmetry (LDF) was used. Results. Determination of the age dynamics of the tissue blood flow in subjects aged 17-21 years showed that the parameter of microcirculation in the subjects increased from minimal values at 17 years to maximal values at 21 years. In the female subjects, the value of the microcirculation parameter was higher at 17 years than in the male subjects, while the maximum perfusion value for girls was at 19 years and at 20 years in the male subjects. Assessment of the regulatory devices showed that the amplitude value of low-frequency oscillations in females fell at the age of 19 years and in males at 20 years. The maximal amplitude index of vasomotor oscillations was registered at the age of 19 years both for boys and girls. The amplitude of vasomotor oscillations in the high-frequency range varied in both girls and boys. Three types of LDF-grams were identified among the young adolescents: aperiodic LDF-grams, which correspond to normoemic type of microcirculation, monotonous low amplitude LDF-grams, which correspond to hypooemic type of microcirculation, sinusoidal LDF-grams, which correspond to hyperemic type of microcirculation. Conclusions. As many studies have shown, the heterochronicity of values of blood microcirculation indices is preserved in male and female subjects: in one age section the indices are higher in females, in the other one – in adolescents. This fact reflects the general biological regularity of different maturation of male and female organisms